FE2+-MG2+ PARTITION BETWEEN COEXISTING CORDIERITE AND GARNET - DISCUSSION OF EXPERIMENTAL-DATA - Wood, B (Springer-Verlag, 1973)
The partition of iron and magnesium between cordierite and garnet depends on Mathematical expression as well as temperature. The apparently conflicting experimental data on the values of KD may be reconciled by considering the Mathematical expression pertaining during the different experiments. © 1973 Springer-Verlag.